Kinetics and mechanism of graft polymerization of acrylic acid onto starch initiated with ceric ammonium nitrate - Tung, Nguyen Thanh; Khoi, Nguyen Van (Vietnam Journal of Chemistry, 2012)
Graft polymerization of acrylic acid (AA) onto tapioca starch was carried out using ceric ammonium nitrate (CAN) as initiator in aqueous nitric acid medium. The kinetics of the graft polymerization of AA onto starch was studied by gravimetric method. The following rate expression (rate of graft polymerization) Rg = k. [AA]1.02 [CAN]0.478 [Starch]0.543 was obtained and a suitable mechanism was suggested. The overall activation energy was found to be 41.33kJ/mol within the temperature range of 30 - 40oC.